2004
DOI: 10.1161/01.str.0000144682.00822.83
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Intra-arterial Papaverine Preserved with Chlorobutanol Used for the Treatment of Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Papaverine is used to vasodilate cerebral arteries undergoing vasospasm from subarachnoid hemorrhage. However, papaverine inhibits cellular respiration in vitro and could cause neurotoxicity in humans. Methods-We studied 5 consecutive patients with cerebral vasospasm who were treated with intra-arterial papaverine preserved with chlorobutanol and imaged with MRI fluid-attenuated inversion recovery and diffusion-weighted imaging after treatment. One patient had histological analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 18 publications
1
41
0
1
Order By: Relevance
“…one study demonstrated high signal intensity on diffusion-weighted and fluid-attenuated inversion recovery MrI at the gray matter within the vascular territories treated with papaverine, and concordant neuronal injury upon pathological examination 38 . In animal studies, opening of the blood brain barrier and endothelial cell injury after papaverine infusion were reported 39,40 .…”
Section: Differences In the Drug Pathomechanismsmentioning
confidence: 94%
“…one study demonstrated high signal intensity on diffusion-weighted and fluid-attenuated inversion recovery MrI at the gray matter within the vascular territories treated with papaverine, and concordant neuronal injury upon pathological examination 38 . In animal studies, opening of the blood brain barrier and endothelial cell injury after papaverine infusion were reported 39,40 .…”
Section: Differences In the Drug Pathomechanismsmentioning
confidence: 94%
“…231 Papaverine is used less frequently because it can produce neurotoxicity. 232 The primary limitation of vasodilator therapy is the short duration of benefit. As with hemodynamic augmentation, there have been no randomized trials of these interventions, but large case series have demonstrated angiographic and clinical improvement.…”
Section: Management Of Cerebral Vasospasm and DCI After Asahmentioning
confidence: 99%
“…Intraarterial papaverine was the first drug to be tested and has been widely used in patients with symptomatic CVS, but no outcome improvement could be demonstrated in comparison to standard medical treatment. 9 Moreover, papaverine is associated with serious neurotoxic side effects including: severe brain stem depression, increased intracranial pressure, mydriasis, neurological deficits, seizures, and coma, 10 possibly related to precipitation of papaverin hydrochloride crystals. 8 Various calcium channel blockers have also been administered as intraarterial infusion.…”
Section: Tarabini Fraticelli Et Al Milrinone For Vasopasm After Subarmentioning
confidence: 99%